Learning path : dive deeper into PHP programming. - Powers, David; Bierer, Doug; Mitchell, Lorna Jane; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2015)
"After 11 long years, we're seeing the release of PHP 7, the first major version since PHP 5.0. With this Learning Path, you'll get up to speed quickly with PHP 7, as you explore the new language features, important fixes, and more. Then, you'll take your skills even further as you master PHP web services and security. This Learning Path is what you need to bring your PHP sites and apps current with the modern web."--Resource description page.
Up to Speed with PHP 7 / with David Powers -- PHP Web Services / with Lorna Jane Mitchell -- PHP Security, by Doug Bierer.
Title and publication information from resource description page (Safari, viewed March 15, 2016).
Presenters, David Powers, Doug Bierer, Lorna Mitchell.
Keywords: PHP (Computer program language); Scripting languages (Computer science); Web site development; Electronic books